2019
DOI: 10.1155/2019/3598404
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Banking: Antenatal Care Provider’s Roles and Responsibilities

Abstract: Background. Umbilical Cord Blood (UCB) banking done either for private storage or for donation to public cord blood banks involves active participation of obstetricians. Counseling the expectant parents, providing them with unbiased and balanced information, and collecting the UCB with diligence confer a lot of social as well as moral responsibility upon obstetricians. This makes it even more important that the obstetricians in current practice stay well-informed and updated with UCB collection and its storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…One can conclude that the less knowledge the health professional has, the poorer the consultation will be, and the rate of UBC banking will remain low. These conclusions are also suggested by others [ 25 , 26 ]. In most countries there are two possibilities for cord blood banking: by donation in public banks or by user-pays storage for private use [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…One can conclude that the less knowledge the health professional has, the poorer the consultation will be, and the rate of UBC banking will remain low. These conclusions are also suggested by others [ 25 , 26 ]. In most countries there are two possibilities for cord blood banking: by donation in public banks or by user-pays storage for private use [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…In Poland, that phenomenon can be connected with advertising and a strong private network of cord blood banks, which store cord blood for future use by the donor or his/her relatives. However, many studies have also demonstrated a positive attitude towards cord blood donation, even towards public storage [ 30 , 31 ]. The results obtained show that some pregnant women knew that additional perinatal tissues containing stem cells with potential therapeutic value are routinely discarded as medical waste.…”
Section: Discussionmentioning
confidence: 99%
“…A review of UCB awareness studies found contradictory findings [8]. A number of studies reported a high level of awareness of UCB banking among women [9], [10], [11], while others reported a low level of awareness [7], [12], [13]. Further, knowledge and awareness of UCB banking among health professionals were relatively low [5], [14] despite these health professionals being identified by expectant parents as their preferred, key sources of information [5].…”
Section: Introductionmentioning
confidence: 99%
“…According to Peberdy et al [5], [8], most of the current studies were focused on professionals, donors, pregnant women, or potential parents. There are only a few studies involving general public [9], [13]. The majority of studies reported that personal characteristics, such as age and education, did not matter when evaluating UCB banking.…”
Section: Introductionmentioning
confidence: 99%